Predictive value and robustness of the stress hyperglycemia ratio combined with hypertension for stroke risk: evidence from the CHARLS cohort - Yaxuan He; Yu Cao; Rong Xiang; Fang Wang (Cardiovascular Diabetology)
Abstract Background Stroke remains a major cause of death and long-term disability worldwide, particularly in low- and middle-income countries. Early identification of individuals at high risk is essential for prevention. The stress hyperglycemia ratio (SHR), a novel indicator integrating acute and chronic glycemic states, has shown prognostic value in acute illness. However, its association with stroke risk in community populations and its potential interaction with hypertension remain unclear. Methods This retrospective cohort study included 9682 stroke-free participants aged ≥ 45 years from the 2011 baseline of the China Health and Retirement Longitudinal Study (CHARLS), followed through 2020. SHR was calculated using fasting blood glucose and glycated hemoglobin. Participants were categorized by median SHR and hypertension status into four groups. Cox proportional hazards models were used to assess associations with incident stroke over a median follow-up of 8.43 years. Subgroup, stratified, and sensitivity analyses were performed. Predictive performance was evaluated using receiver operating characteristic (ROC) curve analysis. Results During 81,601 person-years of follow-up, 764 incident stroke cases were documented, with an overall incidence of 9.36 per 1000 person-years. Compared to the reference group (low SHR without hypertension), those with high SHR and hypertension had the highest stroke risk (hazard ratio: 2.94, 95% confidence interval: 2.38–3.64). SHR and hypertension were independently associated with stroke risk, and their combination demonstrated a dose-response relationship. Subgroup analyses confirmed consistent findings across sex and age strata. The combined SHR-hypertension model showed improved discriminative ability (area under the ROC curve: 0.653). Sensitivity analyses confirmed the robustness of the results. Conclusions Elevated SHR is independently associated with an increased risk of stroke, and its predictive value is enhanced when combined with hypertension. SHR may serve as an integrated metabolic marker reflecting both acute stress and chronic risk burden. Incorporating SHR into stroke risk assessment tools may improve early identification and enable more targeted prevention strategies, particularly in hypertensive populations.